VARIASI POLA SIDIK JARI MAHASISWA BERBAGAI SUKU BANGSA DI KOTA MADIUN - Karlina Purbasari (UNIVERSITAS PGRI MADIUN, 2017)
The research aimed to find the distribution of fingerprint pattern and the total ridge of students from various ethnis in Madiun. The research was conducted in five Universities in Madiun using Proportional Stratified Random Sampling method. The taking of the fingerprint was conducted by pressing the fingers of each student on the ink pad and the press them on the while paper. The fingerprint patterns were counted by percentage of each pattern and the total ridges of each ethnic were counted by average. The result of the research showed that 10 ethnic had a higher percentage of loop pattern out of 11, they are Javanese (60,4%), Dayak (69%), Flores (50,59%), Batakese (56%), Lampung (90%), Balinese (70%), Mentawai (50%), Banjar (60%), Madurese (100%), and Betawi (70%). Minang ethnic had a higher whorl pattern than other patterns, that is 70%. The highest average of the total ridge could be found in Batakese 196,33 while the lowest average of the total ridge could be found in Madurese 70. It can be concluded that there was different percentage of each pattern and each total ridge in 11 ethnic.